Balanced scorecards and operational dashboards with microsoft excel : 2nd edition - Person, Ron (Gildan Audio, 2018)
Learn to maintain and update scorecards and dashboards with Excel Balanced Scorecards and operational dashboards measure organizational performance and Microsoft Excel is the tool used worldwide to create these scorecards and dashboards. This book covers time-proven step-by-step processes on how to guide executive teams and managers in creating scorecards and dashboards. It then shows Excel developers how to create those scorecards and dashboards. This is the only book that converts theory into practice. The author addresses the people and processes you need to identify strategy and operational metrics and then implement them in dashboards in three versions of Excel. You'll learn how balanced scorecards help organizations translate strategy into action and the ways that performance dashboards enable managers monitor operations. - Covers Excel 2010 back to Excel 2003 - Shows how to develop consensus on strategy and operational plans with the executive teams - Details steps in creating tactical action plans - Gives step-by-step guidance in creating the most powerful management dashboards - Puts over ten years of experience in one book Balanced Scorecards & Operational Dashboards with Microsoft Excel, Second Edition is the ultimate resource for enhancing your strategic and operational performance.